2016
DOI: 10.1111/ced.12889
|View full text |Cite
|
Sign up to set email alerts
|

Novel MBTPS2 missense mutation causes a keratosis follicularis spinulosa decalvans phenotype: mutation update and review of the literature

Abstract: Keratosis follicularis spinulosa decalvans (KFSD) is an X-linked condition characterized by keratotic follicular papules and progressive alopecia, which is caused by mutations in the MBTPS2 gene. We carried out a genetic study on a child who was suspected clinically to have KFSD. Sanger sequencing was performed to detect mutations in the entire coding region of MBTPS2. A novel missense mutation (c.599C>T) was identified in the patient, confirming a diagnosis of KFSD. We reviewed related cases with MBTPS2 mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Glycerol kinase 5 (GK5) inhibits SREBP processing; however, the mechanism through which this occurs is unknown . Mutations to MBTPS2 are associated with IFAP and KFSD in which alopecia is present . C, Representation of putative cholesterol transport and trafficking routes in hair follicle keratinocytes.…”
Section: Cholesterol Homeostasis: a Cellular Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycerol kinase 5 (GK5) inhibits SREBP processing; however, the mechanism through which this occurs is unknown . Mutations to MBTPS2 are associated with IFAP and KFSD in which alopecia is present . C, Representation of putative cholesterol transport and trafficking routes in hair follicle keratinocytes.…”
Section: Cholesterol Homeostasis: a Cellular Overviewmentioning
confidence: 99%
“…[107] Mutations to MBTPS2 are associated with IFAP and KFSD in which alopecia is present. [116][117][118][120][121][122][123][124][125][126][127] C, Representation of putative cholesterol transport and trafficking routes in hair follicle keratinocytes. Uptake of cholesterol is represented by the presence of the LDL receptor (LDLR) and scavenger receptor class B member 1 (SRB1) on the plasma membrane.…”
Section: Chole S Terol Fun C Ti On In K Er Atino C Y Te Cell B I Olmentioning
confidence: 99%
“…For symptomatic relief emollients, topical steroid, and keratolytic agents can be used [4]. Different systemic treatments including isotretinoin, etretinate, dapsone and antibiotics have been tried with varied results it is suggested that the use of retinoids in the early and more active phase of the disease, when histopathology shows perifollicular infiltrate, can bring some benefit [4,6,7]. Treatment is even more disappointing when the disease predominantly shows cicatricial changes, as in this present study [8].…”
Section: Discussionmentioning
confidence: 68%
“…KFSD results from mutations in the MBTPS2 gene. Mutations in this gene also underlie ichthyosis follicularis, alopecia and photo- phobia syndrome [4]. The differential diagnosis of KFSD include icthyosis follicularis alopecia photophobia (IFAP) syndrome (which is characterized by non-scarring alopecia), lichen planopilaris, and lichen spinulosus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation